Deterrence and Strategic Culture : Chinese-American Confrontations, 1949-1958 - Zhang, Shu Guang, 1956 October 31- (Cornell studies in security affairs., 1992)
Does strategic thinking on the question of deterrence vary between cultures? Should practitioners assume a common understanding of deterrence regardless of national and cultural differences? Shu Guang Zhang takes on these questions by exploring Sino-American confrontations between 1949 and 1958. Zhang draws on recently declassified U.S. documents and previously inaccessible Chinese Communist Party records to demonstrate that the Chinese and the Americans had vastly different assessments of each other's intentions, interests, threats, strengths, and policies during this period.